ICSI outcome in surgically retrieved sperm compared with ejaculated sperm control - S. Vishwekar, Pallavi; Lad, Nikita; Shivtare, Mamta; Shetty, Pradnya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Globally, the prevalence of infertility is around 10% of the total population. 30% of these have male factor infertility. Azoospermia is found in 1% of men, in 20% of which, the etiology is a bilateral obstruction of the male genital tract while others have non obstructive azoospermia. In azoospermic men sperms are microsurgically retrieved from epididymis and testes by TESA and PESA respectively. The aim of this study was to evaluate the outcomes of intracytoplasmic sperm injection ICSI using surgically retrieved sperm of azoospermic men either obstructive or nonobstructive and to compare it with ejaculated sperms in men having severe oligospermia. Methods: This was retrospective cohort study conducted based on the data collected from our reproductive endocrinology and infertility unit, 126 ICSI cycles performed during the period of 5 years were taken and divided into two groups, one with patients having ejaculated sperms with oligospermia and other group with patients who had surgically retrieved normal sperms due to azoospermia. Outcome of these ICSI cycles included fertilization, cleavage, biochemical and clinical pregnancy was assessed. Results: In present study it was found that ICSI outcome was comparable in both the groups with ejaculated sperm and surgically retrieved sperm as fertilization rate (72% vs 65%), Implantation Rate (58 vs 51%), clinical pregnancy rate (CPR) (51% vs 44.82%) observed with ejaculated or retrieved sperm group respectively showed no statistical difference. Conclusions: Present study shows that minimally invasive techniques of PESA and TESA can be successfully performed to retrieve sperm for ICSI in the treatment of azoospermic men which gives them the chance to father their biological child. The result of this study indicates that treatment outcomes of PESA/TESA-ICSI cycles compare favourably with that of ICSI using ejaculated sperm.